Jak3 Selectively Regulates Bax and Bcl-2 Expression To Promote T-Cell Development - Wen, Renren (American Society for Microbiology, 2001)
Jak3-deficient mice display vastly reduced numbers of lymphoid cells. Thymocytes and peripheral T cells from Jak3-deficient mice have a high apoptotic index, suggesting that Jak3 provides survival signals. Here we report that Jak3 regulates T lymphopoiesis at least in part through its selective regulation of Bax and Bcl-2. Jak3-deficient thymocytes express elevated levels of Bax and reduced levels of Bcl-2 relative to those in wild-type littermates. Notably, up-regulation of Bax in Jak3-deficient T cells is physiologically relevant, as Jak3 Bax double-null mice have marked increases in thymocyte and peripheral T-cell numbers. Rescue of T lymphopoiesis by Bax loss was selective, as mice deficient in Jak3 plus p53 or in Jak3 plus Fas remained lymphopenic. However, Bax loss failed to restore proper ratios of peripheral CD4/CD8 T cells, which are abnormally high in Jak3-null mice. Transplantation into Jak3-deficient mice of Jak3-null bone marrow transduced with a Bcl-2-expressing retrovirus also improved peripheral T-cell numbers and restored the ratio of peripheral CD4/CD8 T cells to wild-type levels. The data support the concepts that Jak kinases regulate cell survival through their selective and cell context-dependent regulation of pro- and antiapoptotic Bcl-2 family proteins and that Bax and Bcl-2 play distinct roles in T-cell development.